Persepsi Mahasiswa Akuntansi atas Penggunaan E-Learning pada Masa Pandemi Covid-19 dengan Pendekatan Technology Acceptance Model - Christony Maradesa; Andreuw Pantow; Ivoletti Merlina Walukow; Esrie Alfian Nixon Limpele; Raymond Festus Rombot (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
This study aims to examine the factors that influence the intention of accounting students to use e-learning. This research uses the Technology Acceptance Model (TAM) construct. Data collection was carried out through a survey with a questionnaire to accounting students at Politeknik Negeri Manado. Analysis of research data using Partial Least Square. The results showed that when students felt the benefits and convenience of using e-learning it made them have the intention to accept the use of these applications